(untitled) (Fiep Bulletin - online, 2011)
In units of the Family Health Program the major skin diseases identified by the health team are: impetigo, skin abscess, cellulitis, dermatitis, pruritus, urticaria, erythema, sunburn, skin changes due to radiation exposure, nail disorder, alopecia, acne, ulcer. This article aims describes the main skin problems evidenced in the Family Health Program in the brazilian scientific literature, as the author, year, type of study and approach, type of injury and treatment adopted. The research is a descriptive (literature review) and quantitative approach, carried out in the BVS, SCIELO Brazil, Scholar google, scientific journals related to areas of public health and dermatology available electronically, using the key words "skin diseases" and "Program Family Health ", with works published between the years 2005 to 2009, in the form of the full text. During the collection, were found 9 products: 4 in SCIELO BRAZIL, 4 on Scholar google and 1 in the Journal of Nursing of the Federal University of Pernambuco On Line (REUOL). In the other sources of information there are no studies that met the inclusion criteria. The data collected were sketched on a table for better understanding. Most studies were located in SCIELO Brazil (44.4%) and Scholar google(44.4%) in the years 2005 (33.3%) and 2005 (33.3%), using the descriptive study (88.9%) and literature review (11.1%), with a qualitative approach (77.8%). The predominant injuries were varied, with emphasis of mycoses (55.6%), which are treated with antifungal and hygiene measures. Skin diseases have significant impact on quality of life of affected and may be limiting, cause absenteeism at school and at work and often act negatively on one’s social life, especially in the chronically ill. Is therefore necessary your valorization as health problems for which public policies should be properly formulated.